Simulation based calculation of the inverse kinematics solution of 7-DOF robot manipulator using artificial bee colony algorithm - Dereli, Serkan; Köker, Raşit (SN applied sciences, 2020)
This paper presents an artificial bee colony algorithm for solving the inverse kinematics of 7-degree-of-freedom robotic arm which has been newly designed and not used in the literature. The kinematics analysis of this manipulator which has an excessive number of joints, is quite complex. In this study, artificial bee colony, which is one of the swarm-based heuristic algorithms, has been used for inverse kinematics solution and its results have been analyzed in terms of position error and calculation time. In order to ensure the accuracy of the algorithm, calculations have been also carried out in 100 different points selected from the workspace of the robot manipulator. The results have been compared with particle swarm optimization, which is another swarm algorithm in terms of position error and computation time. The results obtained by computer simulation clearly show that the artificial bee colony algorithm produces effective results compared with the literature.